Reflection on the Role of the Family Hope Program (PKH) in Poverty Alleviation - Widayat, Widayat; Sugiyanto, Sugiyanto (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. Poverty remains a significant challenge in developing countries, including Indonesia, where over 25 million people live below the poverty line. The Family Hope Program (Program Keluarga Harapan, PKH) was introduced to provide direct assistance to low-income families, aiming to improve their quality of life and break the cycle of poverty. This study focuses on the implementation of PKH in Pagerharjo Village, Kulon Progo, Yogyakarta, using a descriptive qualitative approach involving observation, interviews, and document analysis. The findings indicate that PKH has a positive impact on improving community welfare, particularly in access to education and healthcare services. However, challenges such as inaccurate beneficiary targeting, low program literacy among recipients, and a culture of dependency continue to hinder the program's effectiveness. To enhance the success of PKH, regular validation of recipient data, integration of economic empowerment programs, and structured and continuous education for beneficiaries are essential. This study reflects critically on PKH implementation and offers practical insights for improving local-level targeting and beneficiary engagement. With these measures, PKH is expected to be more effective in promoting sustainable poverty reduction and fostering long-term self-reliance. Keywords: PKH, Social Assistance, Poverty Alleviation, Economic Empowerment, Social Welfare, Reflection. Abstrak. Kemiskinan tetap menjadi tantangan utama di negara berkembang, termasuk Indonesia, dengan lebih dari 25 juta orang hidup di bawah garis kemiskinan. Program Keluarga Harapan (PKH) diperkenalkan untuk memberikan bantuan langsung kepada keluarga berpenghasilan rendah, dengan tujuan meningkatkan kualitas hidup dan memutus rantai kemiskinan. Penelitian ini berfokus pada implementasi PKH di Desa Pagerharjo, Kabupaten Kulon Progo, Yogyakarta, dengan pendekatan deskriptif kualitatif yang melibatkan observasi, wawancara, dan analisis dokumentasi. Hasil penelitian menunjukkan bahwa PKH memberikan dampak positif dalam meningkatkan kesejahteraan masyarakat, khususnya dalam akses terhadap pendidikan dan layanan kesehatan. Namun, tantangan seperti ketidaktepatan dalam penentuan sasaran penerima, rendahnya pemahaman program oleh penerima manfaat, dan budaya ketergantungan masih menghambat efektivitas program. Untuk meningkatkan keberhasilan PKH, diperlukan validasi data penerima secara berkala, integrasi program pemberdayaan ekonomi, serta pendidikan yang terstruktur dan berkelanjutan bagi penerima manfaat. Studi ini merefleksikan secara kritis pelaksanaan PKH dan memberikan masukan praktis untuk memperbaiki sasaran program serta keterlibatan penerima di tingkat lokal. Dengan langkah-langkah tersebut, PKH diharapkan dapat lebih efektif dalam mendorong pengurangan kemiskinan yang berkelanjutan dan membangun kemandirian jangka panjang. Kata Kunci: PKH, Bantuan Sosial, Pengentasan Kemiskinan, Pemberdayaan Ekonomi, Kesejahteraan Sosial, Refleksi.